Studi Komparasi Hasil Belajar Matematika Menggunakan Pendekatan Terbuka Dan Tertutup Siswa Kelas VIII Smp Negeri 2 Plupuh Tahun Ajaran 2015/2016 - Astuti, Winda, Idris Harta M.A., Ph.D (2016)
The aim of this study was to know the difference of the result of mathematic learning between using open and close approach for grade VIII students of SMPN 2 Plupuh in 2015/2016 academic year. The kind of the study based on quantitative approach. The population of this study was grade VIII students of SMPN 2 Plupuh. The sample of this study was 62 students which chosen using cluster random sampling technique. The method that was used in collecting data were test and documentation. The analysis technique used T-test which needed requirement test, homogenity test and normality test. Based on the study of data analysis with 5% of significance, we get the result tcount = 2,303 > ttable = 1,671, therefore the condision, H0 was not appropriate. It means there was difference mean between using open and close approach. Therefore we could conclude that the learning result using open approach was better than using close approach.